THE DIFFERENCE OF PREDICTED AND FINAL REFRACTION USING BU-II AND SRK/T FORMULA IN HIGH MYOPIA PATIENT AT DR. KARIADI HOSPITAL - Irlinda, Riva; Fatimah Dyah Nur Astuti; A. Kentar Arimadyo Sulakso; Wisnu Sadasih; A. Rizal Fanany (Majalah Oftalmologi Indonesia, 2023)
Introduction: Studies showed 38% refractive errors after intraocular lens (IOL) implantation are caused by deviations in calculation of IOL power. The difference between the formula’s refractive prediction and patient’s final outcome highly increases in cases of high myopia, but needs to be more research on this topic. This study aims to show difference between predicted and final refractive outcomes using Barrett II Universal (BU-II) and SRK/T in patients with high myopia who underwent phacoemulsification and IOL implantation. Method: This analytical observational study with cross-sectional design was conducted on high myopia patients (axial length ? 26.0 mm) who underwent phacoemulsification and intraocular lens implantation between January 2021 and January 2022 at Dr. Kariadi General Hospital Semarang. Data used in this study consisted of biometric measurements and difference between predicted refractive outcomes using BU-II and SRK/T formulas and final refractive outcomes of patients one month after surgery. Data were analyzed using one-sample T-test, and significance level of p < 0.05 was considered statistically significant. Results: Thirty-five eyes participated in this study, the mean axial length was (29.33  2.01). BU-II formula has mean difference in refraction prediction with patient's final refraction result closer to zero (1.191.31) than SRK/T formula (1.25  1,12). The difference between two formulas was statistically significant (p < 0.05). Conclusion: The BU-II formula has lower difference between predicted and final refractive outcomes of high myopia patients after phacoemulsification and IOL implantation than SRK/T formula.